Spontaneous emergence of straintronics effects and striped stacking domains in untwisted three-layer epitaxial graphene - Rejhon, Martin; Parashar, Nitika; Schellack, Lorenzo; Shestopalov, Mykhailo; Kunc, Jan; Riedo, Elisa (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Emergent electronic phenomena, from superconductivity to ferroelectricity, magnetism, and correlated many-body band gaps, have been observed in domains created by stacking and twisting atomic layers of Van der Waals materials. In graphene, emergent properties have been observed in ABC stacking domains obtained by exfoliation followed by expert mechanical twisting and alignment with the desired orientation, a process very challenging and nonscalable. Here, conductive atomic force microscopy shows in untwisted epitaxial graphene grown on SiC the surprising presence of striped domains with dissimilar conductance, a contrast that demonstrates the presence of ABA and ABC domains since it matches exactly the conductivity difference observed in ABA/ABC domains in twisted exfoliated graphene and calculated by density functional theory. The size and geometry of the stacking domains depend on the interplay between strain, solitons crossing, and shape of the three-layer regions. Interestingly, we demonstrate the growth of three-layer regions in which the ABA/ABC stacking domains self-organize in stable stripes of a few tens of nanometers. The growth-controlled production of isolated and stripe-shaped ABA/ABC domains open the path to fabricate quantum devices on these domains. These findings on self-assembly formation of ABA/ABC epitaxial graphene stripes on SiC without the need of time-consuming and nonscalable graphene exfoliation, alignment, and twisting provide different potential applications of graphene in electronic devices.
Keywords: epitaxial graphene; ABC graphene; cAFM